Adverse drug reactions due to cancer chemotherapy in a tertiary care teaching hospital. (February 2017) - Wahlang, Julie Birdie; Laishram, Purnima Devi; Brahma, Dhriti Kumar; Sarkar, Chayna; Lahon, Joonmoni; Nongkynrih, Banylla Shisha
Background: An adverse drug reaction (ADR) is defined by World Health Organization (WHO) as 'Any response to a drug which is noxious, unintended and occurs at doses used in man for prophylaxis, diagnosis or therapy'. ADRs associated with cancer chemotherapy warrant analysis on their severity and preventability. The outcome would create awareness among health care providers and prevent their recurrence. We have performed a hospital-based prospective observational study designed to analyze the pattern of ADRs to chemotherapeutic agents in cancer patients of a tertiary care hospital. Methods: A total of 119 cancer patients were monitored for suspected ADRs during the course of chemotherapy from November 2014 to December 2015. Clinical events were recorded and analyzed with regard to the demographics and drug details of the patients. Results: A total of 106 ADRs were recorded from 119 cases. The ADRs commonly encountered included constipation, nausea, vomiting, alopecia and hematological changes. Cisplatin, cyclophosphamide, paclitaxel and 5-FU were used for the treatment of commonly found cancers in this region affecting the lungs, esophagus and lymphomas. Naranjo's causality assessment showed 86.7% possible (score 4) and 13.2% probable (score 5–6). Severity of adverse reactions showed 77.4% mild, 18.9% moderate and 3.8% severe. A total of 45.3% of ADRs were preventable reactions such as nausea, vomiting and constipation. Conclusions: This study highlights the role of active monitoring as an important tool for early detection, assessment and timely management of ADRs in patients undergoing cancer chemotherapy. The observed ADRs were preventable although ADRs such as hiccough, anemia, neutropenia and alopecia were not preventable.